Sekolah Mode Di Pekanbaru Dengan Pendekatan Arsitektur ART Deco - Maulida, Syadzwana; Amanati, Ratna; Rijal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Fashion school in Pekanbaru is a place of informal education in the field of fashion based Institute of Vocational Education. Fashion is a style that can be expressed through fashion products, so that the same thing happened to the art deco movement that produces an object related to one of the fashion products. Art deco architecture appears as a result of the global changes that produce the trend in expressing of shapes and a new spirit of expression. Base on that, then has decided